PENGARUH PRODUK, LAYANAN DAN KEPUASAN TERHDAP PERILAKU WORD OF MOUTH (Studi Kasus Pada PT Bank Windu Kentjana International, Tbk cabang Pesanggrahan, Jakarta) - Mariah Mariah (JURNAL LENTERA BISNIS, 2015)
Banks are financial intermediaries (financial intermediaries) which is vital to support  the smooth running of the economy. Bank is simply interpreted as a financial institution whose business activities are saving funds from the community and distribute the funds back to the community as well as provide other banking services. The development and improvement of service quality from this company are important to get public attention. It can be seen from the stiff competition in terms of service quality and their promotional that the company do. Under this of intense competition, the main thing that is prioritized by companies which engaged in the field of “service” is customer satisfaction, confidence and excellent service quality in order to increased customer loyalty and believes of Word of mouth. This study conducted to determine the effect of product  (X1) srvice (X2) and Customer Satisfaction (X3) to the conduct word of mouth at the PT Bank Windu Kentjana International Tbk, Pesanggrahan Branch Jakarta. The model used in this research is descriptive and associative models, by using SPSS 19. This study uses sampling techniques such as random sampling technique, with a total sample of 80 people. The research instrument used as a measuring tool in this study is a questionnaire consisting of 40 statements. Research conducted Variable Product (X1), Services (X2) and Customer Satisfaction (X3) simultaneously affect the Behavior of Word of Mouth (Y). From the results of this study concluded, should PT Bank Windu Kentjana International Tbk Jakarta improve products and excellent service to its customers as well as a good prospective customers so that customers become loyal to the company and the Behavior Word of Mouth increasing Keywords: Product, Service ,  Customer Satisfaction and Behavior Word of Mouth